Therapy and rehabilitation of women with diabetic adhesive capsulitis - Iryna Zharova; Yevhen Orlenko (Фізична реабілітація та рекреаційно-оздоровчі технології)
Purpose. The purpose of the work is to scientifically and methodologically substantiate and develop a program of therapy and rehabilitation for mature women with type 2 diabetes mellitus and adhesive capsulitis, in order to improve their functional state, activity and participation.